Importance Of Nonverbal Communication In Teaching - Rincón Aponte, Gloria Jeanette (Ingeniería Solidaria, 2011)
The so-called nonverbal communication comprehends the messages conveyed through gestures, manners, postures and space’s usage; these messages are called “non-verbal signs”. The author presents herreflections about the importance of this type of communication inside classroom, to promote a warm and motivating learning environment. Referring the leading researchers in this field and showing their mostrelevant findings, the paper also emphasizes on the contributions of kinetics, proxemics and chronemics to the study of the messages sent by the body. We point ahead some nonverbal behaviors that teachersshould avoid in class, and how they can achieve assertive communication through their body movements. Finally, it mentions some aspects that improve interaction between teacher and his students, from the nonverbal communication point of view.
Keywords: nonverbal communication; kinetics; proxemics; interaction; teachers; students